Analisis Faktor Yang Mempengaruhi Kinerja Personel Keamanan Penerbangan - Zulaichah Zulaichah (Research and Development Agency of The Ministry of Transportation, 2012)
Security personnel are one of the air personnel who are responsible for the security in the flight activities. The quality of the security personnel’s performance certainly affects the quality of the security in the airports. Hang Nadim Airport Batam is one of the airports located in Indonesian borderlines. This condition encourages the airport authorities to improve the quality of the security personnel’s performance. This study is aimed at recognizing the factors that affect the security personnel’s performance in Hang Nadim Airport. The formed factors can be used as reference in creating policies to improve the security personnel’s performance. The method used in this study is factor analysis. This study uses security personnel’s perception data on factors that affect the employees’ performance in general. Based on the result of the study, there are 5 (five) main factors that affect the security personnel’s performance as follows: (1) management policy in protecting the security personnel; (2) cooperation and solidarity within the security personnel; (3) education, income and reward; (4) work regulations and disciplinary sanctions; (5) job difficulty level.Personel keamanan merupakan salah satu personel penerbangan yang bertugas untuk melakukan pengamanan dalam aktifitas penerbangan. Kualitas kinerja personel keamanan tentu mempengaruhi kualitas keamanan di bandar udara. Bandara Hang Nadim Batam merupakan salah satu bandara yang berada di perbatasan Negara Indonesia. Hal ini memacu pengelola bandar udara untuk meningkatkan kualitas kinerja personel keamanan yang baik. Pengkajian ini bertujuan mengetahui faktor-faktor yang mempengaruhi kinerja personel keamanan di Bandara Hang Nadim. Faktor-faktor yang terbentuk dapat dijadikan sebagai acuan dalam merumuskan kebijakan untuk meningkatkan kinerja personel keamanan. Metode yang digunakan dalam pengkajian adalah analisis faktor. Pengkajian ini menggunakan data persepsi personel keamanan tentang faktor-faktor yang mempengaruhi kinerja karyawan secara umum. Berdasarkan hasil kajian, ada 5 faktor utama yang mempengaruhi kinerja personel keamanan yaitu : (1) kebijakan pimpinan dalam mengayomi personel keamanan, (2) kerjasama dan kekompakan antar personel keamanan, (3) pendidikan, penghasilan dan penghargaan, (4) peraturan kerja atau sanksi disiplin, dan (5) tingkat kesulitan pekerjaan.